THE CONCEPT OF EXISTENTIALISM EDUCATION PHILOSOPHY IN GEGURITAN SELAMPAH LAKU - Panji Tresna, I Gusti Ngurah Agung; Siswadi, Gede Agus (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Education is essentially an effort to humanize humans. With human education, character is formed, by strengthening the cognitive, affective, and psychomotor aspects of students. The style of the student's character will become a unity with what philosophical foundation is used in the education. The context in this study is to explore the concept of existentialism education in Geguritan Selampah Laku by Ida Pedanda Made Sidemen. This study uses a qualitative method with a descriptive approach. The results of this study are 1). In the philosophy of existentialism education emphasizes that humans have full responsibility in determining their own actions. So that in the context of education, students are not only objects, but also as subjects, 2). The existentialism education dimension in Geguritan Selampah Laku emphasizes two principles, namely the aspect of selfhood and also the social aspect. The self-awareness aspect reveals how self-awareness plays a role in the educational process. 3). The social aspect includes disclosing the role of the environment in the educational process and emphasizing usefulness as a principle in education. This aspect is the basic foundation and a benchmark for success in the educational process.